2007
DOI: 10.1097/01.tp.0000284583.15810.6e
|View full text |Cite
|
Sign up to set email alerts
|

Single Nucleotide Polymorphism of CC Chemokine Ligand 5 Promoter Gene in Recipients May Predict the Risk of Chronic Graft-Versus-Host Disease and its Severity After Allogeneic Transplantation

Abstract: The CCL5 promoter gene polymorphism of recipients was associated with the risk of cGVHD and its severity. The current study suggested an involvement of CCL5 in leukocyte trafficking for the development of cGVHD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 29 publications
0
19
1
Order By: Relevance
“…The Hardy-Weinberg equilibrium for the IL-17 gene polymorphism was tested using the Haploview program. 5 Multivariate Cox models were used to evaluate the hazard ratio (HR) associated with the IL-17 polymorphism. Covariates found to be significant in univariate analyses (Pp0.20) were included in the models.…”
Section: Data Management and Statistic Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The Hardy-Weinberg equilibrium for the IL-17 gene polymorphism was tested using the Haploview program. 5 Multivariate Cox models were used to evaluate the hazard ratio (HR) associated with the IL-17 polymorphism. Covariates found to be significant in univariate analyses (Pp0.20) were included in the models.…”
Section: Data Management and Statistic Analysismentioning
confidence: 99%
“…2 Previous investigations have revealed that several single-nucleotide polymorphisms (SNPs), which impact on individual immune response to infections and inflammatory reactions are associated with SCT outcomes including the risk of acute GVHD. [3][4][5][6][7][8][9][10][11][12] IL-17, also known as IL-17A, is the hallmark cytokine of a new T-helper subset termed Th17. [13][14][15][16] gdT cells, macrophages and neutrophils are sources of IL-17 as well.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis was stratified for patients with standard-risk disease and high-risk disease to take into account the already recognized prognostic differences. The variables considered were recipient age at time of transplantation, sex, recipient cytomegalovirus serosta- 32 Multivariate Cox models were used to evaluate the hazard ratio associated with the NKG2D polymorphism. Co-variates found to be statistically significant in univariate analyses (p≤0.10) were included in the models.…”
Section: Nkg2d Genotypingmentioning
confidence: 99%
“…10,11 Supporting the role of CCR5 in GVHD, a single nucleotide polymorphism (SNP) in chemokine ligand 5 (CCL5, also known as RANTES) has been significantly associated with a greater incidence of chronic graft-versus-host disease (cGVHD). 12 The authors of another study 13 demonstrated that recipients with the nonfunctional CCR5⌬32 allele were less likely to develop acute graft-versushost disease (aGVHD), and other authors [14][15][16] have found CCR5 promoter polymorphisms to be predictive of the response to chemotherapy in leukemia and in the likelihood of cytomegalovirus and Epstein-Barr virus reactivation after HSCT.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13][14][15][16] In particular, blockade or lack of the chemokine receptors CCR2 and CCR5 on donor leukocytes by administration of anti-CCR5 antibody or infusion of CCR2 Ϫ/Ϫ T cells reduces the incidence of GVHD in animal models. 10,11 Supporting the role of CCR5 in GVHD, a single nucleotide polymorphism (SNP) in chemokine ligand 5 (CCL5, also known as RANTES) has been significantly associated with a greater incidence of chronic graft-versus-host disease (cGVHD).…”
Section: Introductionmentioning
confidence: 99%